Economic structure and unemployment in Colombia: a VEC analysis - Bonilla Cárdenas, Santiago (Sociedad y Economía, 2011)
The objective of this article is to show that features related to economic structure in Colombia are relevant in order to explain the level of unemployment. By using a VEC model and by analyzing impulse response functions and variance decomposition, it is concluded that increasing the degree of structural development of the economy is a policy that can help reduce unemployment in Colombia.